Penerepan Pembelajaran Game Based Learning Untuk Meningkatkan Motivasi Belajar IPA Di SMP Negeri 3 Satu Atap Taliabu Barat - Harwi, Junatri Natri (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This study aims to determine the application of Game-Based Learning (GBL) in improving student learning motivation in science at SMP Negeri 3 Satu Atap Taliabu Barat. The primary problem underlying this research is low student learning motivation, as evidenced by minimal active student involvement in the learning process. This lack of curiosity about unfamiliar material and a tendency for students to be passive during teacher presentations are also contributing factors. Therefore, innovation in learning methods is needed to create an engaging and enjoyable learning environment. The research method used was Classroom Action Research (CAR), conducted over two cycles. The subjects were 34 ninth-grade students. The research instruments included a learning motivation questionnaire, student activity observation sheets, and documentation of the learning process. The results showed that the application of Game-Based Learning significantly increased student learning motivation, as evidenced by the average increase in Cycle I of 63.36 and Cycle II of 84.93. The Cycle I questionnaire score reached 70% and the Cycle II questionnaire score reached 82%, indicating increased learning motivation, as well as increased student engagement in educational games designed to address science topics. Furthermore, students reported being more enthusiastic and motivated to understand science concepts because learning became more interactive and less monotonous. Therefore, Game-Based Learning can be an effective alternative learning strategy to increase student learning motivation, particularly in science subjects.